ANALYSIS OF THE IMPACT OF SOCIAL MEDIA MARKETING ON CONSUMER BUYING BEHAVIOR IN THE DIGITAL - Finny Redjeki (CV. Adiba Aisha Amira, 2025)
The development of digital technology has driven significant changes in marketing strategies and consumer behavior. Social media has emerged as one of the main channels in building relationships between brands and consumers, as well as influencing various stages in the purchasing decision-making process. This study aims to analyze the impact of social media marketing on consumer purchasing behavior through a literature review approach. Data sources were obtained from relevant national and international scientific journals within the last five to ten years. The results of the literature synthesis show that social media directly and indirectly influences consumer behavior through engagement, trust, and perceived value. This study recommends that business practitioners develop personal and interactive content strategies, while academics are encouraged to continue research with an empirical approach to understand the influence between variables more deeply.